Tele-assessment in limb-girdle muscular dystrophy: Feasibility and reliability of patient-led asynchronous method - Baris, Muhammed; Celik, Halil Ibrahim; Karaduman, Aynur Ayse (Sprınger-Verlag Italia Srl, 2025)
Objective This study aimed to investigate the feasibility and reliability of the six assessment tools commonly used in limb-girdle muscular dystrophy (LGMD) for patient-led asynchronous method: Brooke Scale, Vignos Scale, Fatigue Severity Scale (FSS), Numeric Rating Scale for Pain (NRS-Pain), Modified Barthel Index (MBI), and Nottingham Health Profile (NHP). Methods This study included 40 individuals with LGMD (55% female; mean age = 30.53 +/- 9.68 years). The assessment tools used in the study were initially completed by the participants using the patient-led asynchronous method and one week later using the clinician-led synchronous method. Google Forms was utilized for the patient-led asynchronous method, and ZoomTM was used for the clinician-led synchronous method. Furthermore, a questionnaire created by the researchers was administered to assess the satisfaction and usefulness of the procedures of both tele-assessment methods. Results There was no significant difference between the total scores of the six assessment tools obtained by both methods (p's > 0.05). Intraclass correlation coefficients (ICC) exhibited excellent reliability for the total scores of the FSS (ICC = 0.91), MBI (ICC = 0.92), and NHP (ICC = 0.87). Weighted kappa (kappa w) showed excellent reliability for the Brooke Scale (kappa w = 0.94) and Vignos Scale (kappa w = 0.94), and good reliability for the NRS-Pain (kappa w = 0.63). The questionnaire conducted on the satisfaction and usefulness of the procedure of tele-assessment methods showed significantly greater overall satisfaction with the clinician-led synchronous method (p = 0.009). Conclusion In individuals with LGMD, the six assessment tools were feasible and reliable when utilized with the patient-led asynchronous method.
Keywords: Limb-girdle muscular dystrophy; Telemedicine; Physiotherapy; Functional capacity; Reliability